'Balancing on a Razor's Edge': Running the Radical Feminist Lesbian Onlywomen Press. Issue 3 (2nd October 2021) - Murphy, Gillian
Abstract: This article follows the story of Onlywomen Press as told from the archives they created, which are now available in the Women's Library at LSE. Onlywomen Press was Britain's first radical feminist lesbian printing and publishing company. Founded in 1974, the press had two aims: to publish lesbian women's writing and to enable women to control the print production process itself. Being part of the women's liberation movement meant not only recognizing their oppression but also opting out of the mechanisms that supported that oppression and creating new ways of working. This article will show that while their vision remained constant, it was extremely difficult to achieve and remain financially solvent.